Speed control of switched reluctance motor via fuzzy fast terminal sliding-mode control. (December 2019) - Divandari, Mohammad; Rezaie, Behrooz; Ranjbar Noei, Abolfazl
Abstract: This paper proposes a novel speed-control scheme for switched reluctance motor (SRM) drive based on a fast terminal sliding mode control (FTSMC) method. In addition to its robustness against parameter uncertainties and payload disturbance, finite-time convergence in the presence of external disturbance is guaranteed, and the gain value of a sign function is considerably reduced by combining the proposed FTSMC with a fuzzy logic compensator. To evaluate the quality of the proposed method, it is compared with the proportional–integral and conventional sliding mode control (SMC) methods in both time and frequency domains. The simulation results are obtained using MATLAB™/SIMULINK Ⓡ under various speeds and load-torque conditions. Furthermore, practical results are obtained on a three-phase 12/8-pole SRM by digital signal processor-based controller. The results demonstrate that the proposed controller not only provides faster response than the conventional SMC but also chattering effects are considerably reduced even under abnormal conditions.